The impact of the outdoor design and architectural dimension of Masjid Shas towards microclimate - Abdul, Aslina; Mohamad Nasir, Nur Ikma; Abu Bakar, Aniza; Abdul Malek, Nurhayati; Othman, Rosniza; Sanusi, Aliyah Nur Zafirah (2014)
Physical development has significant effect on the microclimate. Understanding this relationship may contribute towards design improvement. For the context of hot-humid regions, not much research is being done on the impact of outdoor design and its microclimate on the indoor microclimate of a masjid. The aim of this research is to investigate the impact of outdoor design in shaping the outdoor microclimate, followed by their impact on the indoor microclimate of the main prayer hall where majority of masjid users occupy most of the time. Masjid Sultan Haji Ahmad Shah (Masjid SHAS) is surrounded by courtyards on the north, south, east and west, and these courtyards are further surrounded by buildings. The methods of this study consist of three parts, which the first part is field observation of the ground surfaces and architectural dimension. The second part is field measurement of several environmental data such as solar radiation, relative humidity, air temperature, wind direction, wind speed, and surface temperature for the outdoor, air temperature and relative humidity for the indoor environment. The third part is shadow analysis of the masjid in computer simulation software AutoCAD and Google Sketch Up. Analysis on the outdoor and indoor microclimate as shaped by the physical design was carried out and further analyzed to see the co-relationship between these two environments. The finding suggested that the microclimate of indoor environment is directly proportional to the microclimate of the outdoor environment where it is dependent on the outdoor environment